Réponses

2013-02-27T16:02:50+01:00

108) A= 3+4*5+2*(15+3)

A= 3+20+2*(18)

A=23+2*18

A=23+36

A=59

 

 

02) A= 1 sur 9 - 15 sur 9 * 1 sur 6

A =1 sur 9 - 15*1 sur 9*6

A= 1 sur 9 - 15 sur 54

A=1sur 9 -15:3 sur 54:3

A= 1 sur 9 - 5 sur 18

A= 1*2 sur 9*2 - 5 sur 18 A= 2 sur 18 - 5 sur 18 

A= -3 sur 18

 

 

106) A= 1 sur 3 + 5 sur 6 : 3 sur 2

A= 1 sur 3 + 5 sur 6 * 2 sur 3

A= 1 sur 3 + 2*5 sur 6*3

A=1 sur 3 + 10 sur 18

A= 1*6 sur 3*6 + 10 sur 18

A= 6 sur 18 + 10 sur 18

A= 16 sur 18

A= 16:2 sur 18 : 2 

A= 8 sur 9

 

 

86) 1) (3x + 2 ) au carré - ( 5 - 2x) ( 3x + 2)

2)E= (3x + 2) (3x +2) - (5-2x)(3x+2)

E= (3*(-2)+2) (3*(-2) +2) - ( 5-2* (-2)) (3* (-2) +2)

E= ( -6+2) ( -6+2)-(5-4-6+12)

E= -4 -4 - ( 17-10)

E= -8-7

E= -15

 

 

 

 

119) a) 2x -3 = -1

2x = -1+3

2x =2 x

x = 2sur 2

x= 1

 

 

b) 4(x-1) = 2x+3

(x-1) -2x = -4+3

(x-1) -2x= -1

 

 

 

c) x sur 4 = 3 sur 2

x sur 4 = 1.5

x= 1.5 *4

x=6

 

 

 

 

 

120)